Demonstration of a chip-based optical isolator with parametric amplification - Shiyue Hua (Nature Portfolio, 2016)
Non-reciprocal optical elements usually require the presence of magnetic fields, which makes chip integration difficult. Here, Hua et al. demonstrate a non-magnetic optical isolator with bidirectional injection on a silicon platform utilizing parametric amplification in four-wave mixing.